An innovative support pillow for diabetic foot wound care - Suroso, Jebul; Zulfa, Aqilatun; Gumelar, Nanda Cikal; Soleha, Rama Nanda; Nuraeni, Siti; Febriyanti, Ika Putri; Santosa, Agus (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2024)
Background: Treating diabetic foot ulcers (DFU) sometimes takes a long time. During treatment, the patient's feet are usually given a cushion (such as a sleeping pillow or bolster) to make the wound seen. This way, some patients reported that their feet tingled because they were not positioned rightly for an extended period. So far, no unique pillow is available for this function. This pillow would help in treating DFU and should be comfortable for patients. Thus, it is essential to research designing such a product. Purpose: To develop and test a special pillow for treating DFU. Methods: This research adopts Research and Development (R&D). This research is divided into two stages: designing and developing and product testing. Results: This pillow is made of multiplex and foam, covered with Polyester fabric. It is 75mm in length and 45mm in width. It is equipped with a foot care area and waste storage tank. The test results showed that the score for comfort for the patients was 92%, while the score from the nurse was 88%. Conclusion:The pillow product helps the nurse conduct the DFU treatment and is comfortable for the patients. Â 